The Role of the School Principal in Improving the Performance of Elementary School Teachers in Catholic Schools in Samarinda City - Yesepa Yesepa; Usfandi Haryaka; Akhmad Akhmad (EduLine: Journal of Education and Learning Innovation, 2024)
This research aims to describe the leadership of the school principal, obstacles, and efforts in enhancing teacher performance.The research adopts a qualitative method with a case study approach, involving three informants: the school principal, viceprincipal, and teachers. Data collection methods include interviews, observations, and documentation. Data analysis is conductedthrough stages of data collection, reduction, presentation, and conclusion drawing. The research findings indicate that 1) the roleof the school principal as an educator, manager, administrator, supervisor, leader, innovator, and motivator has been executedwell but not yet maximized. 2) Issues such as teacher discipline, limited understanding of technology, lack of enthusiasm, limitedteacher participation in activities, limited human resources, and insufficient support from foundations persist. 3) Mitigationefforts involve joint evaluations, attendance monitoring, training sessions, and building cooperation to create a schoolenvironment that is productive and enthusiastic, thereby maximizing teacher performance. With this approach, the schoolprincipal can energetically optimize teacher performance and enhance the overall effectiveness of the educational process at theschool. Greater support from foundations and relevant stakeholders is also crucial in overcoming limitations in human resourcesand strengthening the role of the school principal as an empowered educational leader